1989
DOI: 10.1088/0953-8984/1/28/001
|View full text |Cite
|
Sign up to set email alerts
|

The reactive element effect; ionic processes of grain-boundary segregation and diffusion in chromium oxide scales

Abstract: Abstract. The transport processes in chromium oxide reviewed here, are related to the basic ionic processes in oxides. Solid state science has been effective in describing the complicated diffusion-controlled oxide growth of chromium and chromia-forming alloys. Additions of reactive elements to chromia-forming alloys have a remarkably beneficial effect and this effect is also related to ionic transport processes in crystal lattices. Chromia-forming alloys are widely used in coal handling and conversion systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…4, it can be concluded that no massive gasesformation at the oxide/carbide interface [23,24], otherwise one would expect a very porous oxide layer and massive cracking of freshly formed Cr 2 O 3 . As dense Cr 2 O 3 film act as the oxygen diffusion barrier [25], the oxidation is controlled by diffusion of oxygen through the full covered Cr 2 O 3 film. Moreover, as the healing effect of pores/pits from the wet oxidation is better than that from the dry oxidation, oxygen transportation during the wet oxidation is smaller than that in the dry oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…4, it can be concluded that no massive gasesformation at the oxide/carbide interface [23,24], otherwise one would expect a very porous oxide layer and massive cracking of freshly formed Cr 2 O 3 . As dense Cr 2 O 3 film act as the oxygen diffusion barrier [25], the oxidation is controlled by diffusion of oxygen through the full covered Cr 2 O 3 film. Moreover, as the healing effect of pores/pits from the wet oxidation is better than that from the dry oxidation, oxygen transportation during the wet oxidation is smaller than that in the dry oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…26,[28][29][30][31][32][33][34] It has also been reported that below 1100 °C oxidation is dominated by short circuit diffusion. 35 That is, the oxide scale grain boundaries are fast diffusion paths for migrating ions. In Y containing or Y 2 O 3 coated alloys, the Y ion in the oxide scale segregates to the grain boundaries and its radius (1.02 Å) being larger than the Cr and Fe ions (0.615 Å and 0.78 Å respectively) blocks the path of the diffusing alloy cations, decreasing thereby the oxidation rate of the alloy.…”
Section: Discussionmentioning
confidence: 99%
“…Grain-boundary diffusion of chromium ions was considered in a previous study to be the main mechanism of steady scale growth on a chromia-forming alloy. [20] Based on the cross-sectional micrographs in Figure 4, it is shown that, while continuing to grow larger, the oxide grains after 60 minutes of oxidation clearly show the tendency of growing into columnar grains (each grain is single crystal in nature) because many oxide grain boundaries are close to being perpendicular to the scale/alloy interface and the scale surface, as well as connecting the two interfaces, as indicated by the arrows in Figure 4. Columnar oxide grains commonly have been observed on alloys oxidized for a relatively long time.…”
Section: Scale Evolution As a Function Of Timementioning
confidence: 99%
“…[32] Although the exact mechanism through which RE ions prohibit diffusion along oxide grain boundaries is not presently agreed on, it is well acknowledged that such segregation suppresses grain boundary diffusion resulting in significant reduction of the scale growth rate below 1273 K (1000°C) when grain-boundary diffusion accounts for approximately 90 to 100 pct of transport through the scale. [20] The presence of the RE ions may reduce the amount of scale forming Cr-ions at the boundaries and consequently may reduce their outward flux and scale growth. (b) It is possible that interactions take place between RE ions and defects at grain boundaries, which create complex defects that reduce the mobility of point defects critical for transport through the scale.…”
Section: Relation Between Observed Diffusion Of Re Into the Scale Andmentioning
confidence: 99%